Mengurangi Limbah Minyak Tanah melalui Pembuatan Sabun Cuci dari Jelantah - Tholib Hariono; Munawaroh Munawaroh; Nurul Yaqin; Nurul Hidayah; Aufia Aisa; Siti Sulaikho (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The purpose of this community service is to reduce household waste from used cooking oil. The approach method for implementing PPTTG includes the Community Development method by means of socialization and demonstration. The method of socialization is carried out by socializing the dangers of using cooking oil repeatedly and the dangers of indiscriminately disposing of used cooking oil waste. The demonstration method is carried out through demonstration of the steps and what must be considered in the use of used cooking oil waste as laundry soap. Through this socialization activity, it is expected to be able to solve the problems faced by Banjarsari village women. Based on the community service activities that have been carried out, the provision of information and demonstrations on the use of household waste is able to increase awareness about the importance of processing waste for health and environmental cleanliness.